Influence Reward and Punishment on The Prevention of Financial Statement Fraud - Olo, Andriana; Rahmadhani, Sari (Indonesia Accounting Research Journal, 2024)
The study aims to examine the effect of rewards and punishments on the prevention of fraud in financial reporting, which is often carried out by the company's financial staff. The results of this study are expected to provide a deep understanding of rewards and punishments in the context of corporate financial integrity. In addition, it can provide practical recommendations for designing a more effective system to overcome financial fraud that occurs in the company. This study uses a quantitative method, data collection through questionnaires distributed to students who are interested in working in the financial sector. The analysis was carried out using multiple linear regression. The hypothesis testing of this study is to identify the factors that affect financial reporting fraud behavior that are linked to the indicators of the company's reward and punishment system. The results of the study show that the reward system can reduce the occurrence of fraudulent behavior in financial statements. Likewise, strict punishment is a means of internal control to reduce the occurrence of corporate financial fraud.